Gambaran Durasi Tidur, Kualitas Tidur dan Status Gizi Mahasiswi di Kota Palu ‎ - Lilik Sofiatus Solikhah (Sekolah Tinggi Ilmu Kesehatan Gunung Sari, 2022)
Entering adolescence, generally lifestyles begin to change, such as lack of sleep for various reasons. Sleep deprivation or short sleep duration in adolescents is associated with poor physical health, mental health, and academic performance. The purpose of this study was to determine the description of sleep duration, sleep quality, and nutritional status of female students in Palu City. This research method was a cross-sectional study with a simple random sampling technique on female students aged 18-23 years who where studying at the University in Palu City. The variables of sleep duration and sleep quality used a Pittsburgh Sleep Quality Index (PSQI) questionnaire and nutritional status used a body mass index (BMI). The results of this study obtained an overview of student sleep duration as much as 21.2% <5 hours, 21.6% 5-6 hours, 24.3% 6-7 hours, and 32.9% >7 hours. The sleep quality of female students is 23.5% good and 76.5% bad. The nutritional status of female students was 25.9% underweight, 54.1% normal, 8.2% overweight, 9.4% obese I, and 2.4% obese II. The conclusion was that the majority of female students had insufficient sleep duration, poor sleep quality, and normal nutritional status.